Storytelling and Trauma: Reflections on “Now I See It,” a digital storytelling project and exhibition in collaboration with the Native Women’s Shelter of Montreal - Deutsch, Rachel; Woolner, Leah; Byington, Carole-Lynn (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
Storytelling is a way of dealing with trauma. For many of those who have experienced trauma, sharing one’s own experiences, in the form of a personal narrative, can help to develop new meaning on past events. Now I See It was a storytelling project that resulted in a collection of photographs taken by members of the urban Aboriginal community of Montreal. The project was run through the Native Women’s Shelter of Montreal in 2014 and exhibited in the educational department of the Montreal Museum of Fine Arts.Now I See It was a way of creating an “‘internal map”’ because trauma is so painfully hard to see and the experience is so different for each individual.